The winners’ drama in Seneca’s Troades - Balula, João Paulo (2018)
Abstract Introduction:The texts of classical literature are of great importance for the formation of critical readers. For this reason, this article proposes a current reading of the winners’ difficulties that are evident in Seneca’s Troades: Pyrrhus, Agamemnon, Ulysses, Achilles, and Helena. Development: Starting from a content analysis of the literary work, a reflection on the consequences of feelings and passions is presented. It becomes evident that when the human being is confronted with himself and with his essence everything comes to the surface: the most admired virtue (moderation) and the most despicable defects (arrogance, brutality, tyranny, hypocrisy and cowardice). Conclusions: It is concluded that the winners’ concern focuses on the doubt about the success of the return trip.